IMPLEMENTASI KURIKULUM KECAKAPAN MENYIMAK KEPADA SANTRI ICBB YOGYAKARTA - Muhammad Syafi'i Tampubolon; Umar Saiful Haq (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
Listening and speaking skills are examples of active skills in Arabic. Students, ustadz, and mudir at Madrasah Aliyah Bin Baz learn many different kinds of language skills. Language skills can be divided into three levels of learning: elementary, intermediate, and advanced. This is a skill that students at Madrasah Aliyah Binbaz Yogyakarta should develop. The language proficiency category is influenced by the teacher's or Ustadz's curriculum. Students at Madrasah Aliyah Binbaz are taught listening or istima' skills such as part of speech, the process of learning listening skills, and the increase of students'